Effect of washed versus unwashed red blood cells on transfusion‐related immune responses in preterm newborns. Issue 3 (9th March 2022) - Crawford, Tara M; Andersen, Chad C; Hodyl, Nicolette A; Robertson, Sarah A; Stark, Michael J
Abstract: Objectives: Transfusion with washed packed red blood cells (PRBCs) may be associated with reduced transfusion‐related pro‐inflammatory cytokine production. This may be because of alterations in recipient immune responses. Methods: This randomised trial evaluated the effect of transfusion with washed compared with unwashed PRBCs on pro‐inflammatory cytokines and endothelial activation in 154 preterm newborns born before 29 weeks' gestation. Changes in plasma cytokines and measures of endothelial activation in recipient blood were analysed after each of the first three transfusions. Results: By the third transfusion, infants receiving unwashed blood had an increase in IL‐17A ( P = 0.04) and TNF ( P = 0.007), whereas infants receiving washed blood had reductions in IL‐17A ( P = 0.013), TNF ( P = 0.048), IL‐6 ( P = 0.001), IL‐8 ( P = 0.037), IL‐12 ( P = 0.001) and IFN‐γ ( P = 0.001). The magnitude of the post‐transfusion increase in cytokines did not change between the first and third transfusions in the unwashed group but decreased in the washed group for IL‐12 ( P = 0.001), IL‐17A ( P = 0.01) and TNF ( P = 0.03), with the difference between the groups reaching significance by the third transfusion ( P < 0.001 for each cytokine). Conclusion: The pro‐inflammatory immune response to transfusion in preterm infants can be modified when PRBCs are washed prior to transfusion. Further studies are required to determine whether the use of washed PRBCs for neonatal transfusion translates into reduced morbidity and mortality. Abstract : This study found that the pro‐inflammatory response to transfusion in very preterm infants is modified when packed red blood cells (PRBCs) are washed prior to transfusion. Further studies are required to determine whether the routine use of washed PRBCs for neonatal transfusion will reduce morbidity and mortality.